The Influence of Concentration and Gravity of the Flotation Solution in the Quantification of Coccidia Oocysts in Feces Samples Using McMaster Technique - Haitham Alnaqeb; Wejdan Alsufayan (Universitas Airlangga, 2026)
Flotation method and McMaster technique are widely used in the field of parasitology. They are used to examine the present and quantity of parasites eggs and oocysts in the fecal samples. They provide quick assessments to evaluate the condition of infection in the host. Nevertheless, there are few quantitative studies regarding testing different concentrations and gravities of the flotation method of Coccidia oocysts. The aim of this study is to evaluate different concentration of the saturated sodium chloride for the quantitating the oocysts of Coccidia via McMaster method. Twenty-seven positive samples were exposed into different concentrations of the saturated sodium chloride (per liter): 360 g, 300g, and 225g. The McMaster technique was used to count the coccidian oocysts in different chosen concentrations for each sample. The results of ANOVA reveal that there is no significant between the concentrations (P > 0.05). The overall finding of this study proposes that lower gravity of NaCl can be used to test the present of coccidian oocysts in the stool sample using the flotation and McMaster methods.